Russian philosophy : volume III : pre-revolutionary philosphy and theology, philosophers in exile, marxists and communists - Edie, James M.; Scanlan, James P.; Zeldin, Mary-Barbara; Kline, George L. (Knoxville : University of Tennessee Press, 1976)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: filosofie; Rusland